ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2015å±Š ä½¿ç”¨åŠ¨é‡è¯â€œæ¬¡â€ã€â€œéâ€å’Œâ€œè¶Ÿâ€çš„åè¯¯åˆ†æž - Mantika, Dwi Citra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2012)
AbstractThe action-measure word is one of the most commonly used phrases in Chinese language, and taking part as the important and difficult subject in Chinese language teaching. In Chinese, there are a lot of action-measure word with almost identical meaning, such as â€œciâ€,â€bianâ€ and â€œtangâ€. Meanwhile, the similiarities of these three words meaning often make students mis-use them in a sentence. Therefore, the researcher conducted a research on the Chinese language students of Tanjungpura University in academic year 2015 in the using of the word â€œciâ€,â€bianâ€ and â€œtangâ€. Based on the data obtained the researcher found the students mis-use error percentage of the word â€œciâ€ was 26,90%, 28,60% for the word â€œbianâ€, and 39,90% for the word â€œtangâ€.Â From the findings, the researcher concluded that the mis-use error could happen due to the influence of the mother tongue andÂ the foreign language. In the end, the researcher also provided some suggestions on learning these three words.Â Keywords: The action-measure word, â€œciâ€, â€œbianâ€ and â€œtangâ€, Â Error analysisÂ